Effect of Aortic Diameter and Systole Blood Pressure on Determination of CTA Coronary Pre-Delay Scan Bolus Trcking Technique - Oesmanto, Arief; Santoso, A. Gunawan; Darmini; Hariri, Ahmad (International Journal of Natural and Health Sciences, 2024)
The variation in the pre-delay scan time of each individual on the CTA Caronaria check bolus tracking will contribute to the total acquisition time and vary the total amount of contrast and copy that must be provided during the acquisition.  This study aims to determine the effect of aortic diameter and systole blood pressure on pre-delay scan time. This research method is observational analytic with a retrospective crossectional approach measuring independent variables of aortic diameter and systole blood pressure. The result are the R Square value is 0.364. The regression coefficient value of  systole blood pressure (X1) is 0.043, the T value that was determined is 3. 102, and the significance value is 0.003. In addition, the computed T value is 3.597, the regression coefficient value of aortic diameter  (X2) is 0.256 and then we founded F value of regression model was 22.072.  As conclusion are Pre-delay scan duration is positively and significantly impacted by aorta diameter, systolic blood pressure has a positive and significant effect on pre-delay scan time and The two variables together have a positive and substantial effect on the pre-delay delay time. Additionally, this study discovered that other parameters controlled 63.6% of the deleye time of contrast material administration, with the remaining 36.4% being influenced by aortic diameter and systole blood pressure